2016
DOI: 10.19126/suje.70220
|View full text |Cite
|
Sign up to set email alerts
|

2009-2013 Yılları Arasında Uzaktan Eğitim Dergilerinde Yayınlanan Makalelerin Yöntemsel Açıdan İncelenmesi

Abstract: Distance Education) son beş yılda yayınlanan makaleleri yöntem kısmı bakımından incelemektir. Araştırma belge incelemesi yöntemi ile gerçekleştirilmiştir. Araştırma kapsamında uzaktan eğitim ile ilgili yayın yapan sekiz derginin son 5 yıl içerisinde yayınladıkları toplam 1233 makale analiz edilmiştir. Çalışmada incelenen makaleler araştırma türü, deseni, örneklem seçimi, örnekleme yöntemi, ölçme aracı ve analiz yöntemi açısından analiz edilmişlerdir. Çalışmadan elde edilen sonuçların uzaktan eğitim alanında ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
(21 reference statements)
1
1
0
1
Order By: Relevance
“…In 7 of the theses (6.3%) Other sampling methods were made use of. According to the existing literature in which the theses and scientific studies are investigated in different science fields, it is observed that similar results were reported with the present study, and the most frequently used sampling methods were Accidental, Random and Purposeful Sampling Methods [55,56,57,58,59].…”
Section: The Results On the Methodology Of The Sports Management Doctsupporting
confidence: 89%
“…In 7 of the theses (6.3%) Other sampling methods were made use of. According to the existing literature in which the theses and scientific studies are investigated in different science fields, it is observed that similar results were reported with the present study, and the most frequently used sampling methods were Accidental, Random and Purposeful Sampling Methods [55,56,57,58,59].…”
Section: The Results On the Methodology Of The Sports Management Doctsupporting
confidence: 89%
“…İncelenen tezlerin kuramsal dayanaklarına bakıldığında ise sırasıyla öğrenme kuramları, uzaktan eğitim kuramları ve iletişim kuramlarının kullanıldığı görülmektedir. Çalışma alanı doğası bakıldığında farklı çalışmalarda da (Bozkaya et al, 2012;Bozkurt et al, 2015a;Davies, 2010;Bozkurt et al, 2015b) (Bozkurt et al, 2015a;Babur et al, 2016;Bozkurt et al, 2015b (Durak et al, 2017). Davies ve ark.…”
Section: Araştırmada Kullanılan Teknolojilerunclassified
“…are examined. It has been determined that the theoretical structure analysis used in the theses in the distance education studies conducted in our country is limited and the studies conducted abroad are more comprehensive (Anglin & Morrison, 2000;Babur et al, 2016).…”
Section: Introductionmentioning
confidence: 99%